Implementation of Performance Management to Increase Employee Productivity - Yasa, I Putu Buda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In this context, this research explores the importance of implementing performance management as a strategy to increase employee productivity. This article will discuss the basic concepts of performance management, effective implementation steps, and the positive impacts that can be obtained from implementing good performance management. By understanding and applying appropriate performance management principles, it is hoped that organizations can achieve sustainable productivity increases, which will ultimately support the achievement of the company's strategic goals. The data collection techniques used were interviews, Participatory Observation, and documentation. This research shows that implementing good performance management can significantly increase employee productivity. Therefore, organizations that wish to improve the performance and productivity of their employees need to adopt a structured, fair and sustainable performance management approach. Thus, the company can achieve its strategic goals and remain competitive in a dynamic market.